Continuous production method of diazonium salt
By controlling the temperature in the tubular reactor and using high-efficiency reaction accelerator, the problem of high-temperature decomposition and explosion risks during diazotization is solved, the purity and yield of diazonium salts are improved, and safe and environmentally friendly continuous production is achieved. .
Patent Information
- Application Number
- CN202411648770.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are problems of high temperature decomposition, explosion risk, low purity and yield during the existing diazotization process, and excessive use of acid leads to increased environmental pollution and risk.
Continuous diazotization is performed using a tubular reactor, the temperature is controlled at 0-5°C, the use of acid treatment graphite provides an acidic environment, and the preparation of reaction accelerators is used to improve heat transfer efficiency and purity, including acid treatment, coating, silane The reaction accelerator with high specific surface area and high activity points is prepared.
Continuous production of diazonium salts has been achieved, the amount of acid is reduced, the purity and yield of diazonium salts have been improved, and the risk of explosion and environmental pollution are avoided.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic synthesis, and in particular to a continuous production method of a diazonium salt. Background Art
[0002] Pyrazolone compounds are a class of heterocyclic compounds containing pyrazolyl and ketone groups. They have strong molecular stability and chemical reactivity and are widely used in the fields of medicine, dyes, etc. In the field of medicine, pyrazolone, as an important pharmaceutical intermediate, can be used to synthesize a series of drugs with anti-inflammatory, antibacterial, analgesic and other effects; in the field of dyes, pyrazolone derivatives are used to manufacture azo dyes.
[0003] The preparation method of pyrazolone compounds mainly includes the following steps: diazotization, reduction, hydrolysis, and condensation, wherein diazotization is a reaction of a primary amine and a diazotization agent at low temperature to generate a diazonium salt. In the reaction, the primary amine combines with the diazotization agent, proton transfer occurs, and finally a diazonium salt is generated. Among them, the primary amine is an aromatic primary amine, and the diazotization agent is nitrous acid. Since nitrous acid is unstable and easy to decompose, during the preparation, aromatic primary amines, sodium nitrite, and acid are usually used as raw materials, and the acid used is mainly hydrochloric acid or sulfuric acid. During the reaction, the acid can promote the aromatic primary amine to dissolve and react with sodium nitrite to generate nitrous acid, and can also promote the reaction of nitrous acid with the aromatic primary amine to generate a diazonium salt, thereby avoiding the decomposition of nitrous acid.
[0004] The main problems in diazotization are: first, since diazotization is a strong exothermic reaction, and sodium nitrite is an inorganic oxidant, which is easy to decompose at high temperature, diazonium salt is extremely unstable and dangerous, easy to decompose, and a large amount of gas will be released during the decomposition of diazonium salt, which will cause a sharp increase in pressure and cause explosion, thereby resulting in high danger of diazotization and low purity and yield of diazonium salt; second, diazonium salt is easy to undergo irreversible coupling reaction with unreacted aromatic primary amine in a neutral or weakly acidic environment, affecting the purity and yield of diazonium salt. In order to avoid the occurrence of coupling reaction, it is necessary to use excess acid to improve the stability of the prepared diazonium salt, but the use of excess acid will aggravate environmental pollution and increase the danger of diazotization; third, at present, industrial diazotization is generally carried out in an intermittent reactor, which has low heat transfer efficiency and discontinuous reaction, resulting in easy decomposition of the prepared diazonium salt, causing explosion, further increasing the danger of diazotization and further reducing the purity and yield of diazonium salt.
[0005] In order to solve the above problems, the inventor tried to carry out diazotization in a tubular reactor, and the temperature of diazotization was controlled at 0-5 ° C, so as to achieve continuity while improving heat transfer efficiency and avoiding the decomposition of diazonium salt. In addition, acid-treated graphite was loaded in the tubular reactor, and the surface of the acid-treated graphite contained a large number of carboxyl groups, so that it could provide an acidic environment by ionizing hydrogen ions and reduce the amount of acid. In addition, the acid-treated graphite can also play a heat dissipation role. Taking the inventor's preparation of 1-phenyl-3-methyl-5-pyrazolone as an example, when diazotization is carried out, aniline is first mixed with acid to obtain a first reactant, sodium nitrite is dissolved in water to obtain a second reactant, and then the tubular reactor is filled with acid-treated graphite, the temperature in the tubular reactor is reduced to 0-5 ° C, and the first reactant and the second reactant are simultaneously introduced into the tubular reactor, the product flowing out of the tubular reactor, i.e., diazonium salt, is collected, and the diazonium salt is stored at low temperature.
[0006] However, in the actual preparation, the following problems are still found: first, since aniline has strong alkalinity and does not contain electron-withdrawing groups in the molecule, it is easy to generate stable ammonium salts with inorganic acids, and the ammonium salts are difficult to hydrolyze. Therefore, when preparing the first reactant, it is necessary to mix aniline with dilute acid, resulting in that after the first reactant and the second reactant are simultaneously introduced into the tubular reactor, the acidity of the reactants in the tubular reactor is weak, and the prepared diazonium salt and unreacted aniline will undergo an irreversible coupling reaction under a weakly acidic environment, resulting in reduced purity and yield of the prepared diazonium salt. Although the acid-treated graphite in the tubular reactor can ionize hydrogen ions, the ability of the acid-treated graphite to ionize hydrogen ions is limited, resulting in poor improvement of the purity and yield of the prepared diazonium salt; second, the acid-treated graphite can adsorb aniline, and since the specific surface area of the acid-treated graphite is large, it can also provide a weakly acidic environment, and the coupling reaction speed of the prepared diazonium salt with aniline on the surface of the acid-treated graphite becomes faster, which will further reduce the purity and yield of the prepared diazonium salt. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a method for the continuous production of a diazonium salt, which can achieve the continuous production of the diazonium salt while reducing the amount of acid used and improving the purity and yield of the prepared diazonium salt.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A continuous production method of a diazonium salt comprises the following steps: preparing a reaction accelerator, preparing equipment, preparing raw materials, and reacting; The preparation of the reaction accelerator comprises the following steps: acid treatment, coating, silanization, and carboxylation; The acid treatment comprises mixing the graphite powder and deionized water, performing ultrasonic oscillation, controlling the frequency of the ultrasonic oscillation to be 25-30kHz, and performing the filtration for 20-30min, performing the filtration, taking the filter residue, performing vacuum drying, and controlling the temperature of the vacuum drying to be 80-90°C, and then mixing with an aqueous nitric acid solution, stirring and refluxing, controlling the temperature of the stirring and refluxing to be 80-85°C, and the stirring speed to be 200-400rpm for 3-3.5h, performing the filtration, taking the filter residue, washing it with deionized water for 4-5 times, performing vacuum drying, and controlling the temperature of the vacuum drying to be 80-90°C, and obtaining the graphite powder after the acid treatment; In the acid treatment, the mass volume ratio of graphite powder, deionized water, and nitric acid aqueous solution is 50-55 g:470-500 mL:500-550 mL; The particle size of the graphite powder is 60 mesh; The mass concentration of the nitric acid aqueous solution is 30%; The coating comprises mixing tetraethyl orthosilicate and deionized water, stirring the mixture, controlling the stirring temperature to be 20-35° C., the stirring speed to be 200-400 rpm, and the time to be 1.5-2 hours, adding anhydrous ethanol, continuing to stir for 2.5-3 hours, adding the first portion of ammonia water, continuing to stir for 2.5-3 hours, adding the graphite powder after acid treatment, continuing to stir for 30-40 minutes, dropping the second portion of ammonia water, continuing to stir for 11-12 hours after the dropping is completed, filtering, taking the filter residue, washing it with deionized water for 4-5 times, and vacuum drying it, controlling the vacuum drying temperature to be 80-90° C., and obtaining the coated graphite powder; In the coating, the volume mass ratio of ethyl orthosilicate, deionized water, anhydrous ethanol, the first portion of ammonia water, the graphite powder after acid treatment, and the second portion of ammonia water is 10-11 mL: 500-525 mL: 400-450 mL: 35-38 mL: 24-26 g: 470-500 mL; The mass concentration of the first ammonia water and the second ammonia water are both 28%; The second portion of ammonia water is added at a rate of 10-15 mL / min; The silanization comprises mixing the coated graphite powder, anhydrous ethanol and deionized water, stirring and refluxing, controlling the temperature during stirring and refluxing to be 55-65° C., the stirring speed to be 200-400 rpm, and the time to be 30-40 min, adding 2-cyanoethyltriethoxysilane, continuing to stir and reflux for 10-12 h in a nitrogen atmosphere, filtering, taking the filter residue, washing it with anhydrous ethanol for 4-5 times, and vacuum drying it, controlling the vacuum drying temperature to be 80-90° C., and obtaining the silanized graphite powder; In the silanization, the mass volume ratio of the coated graphite powder, anhydrous ethanol, deionized water, and 2-cyanoethyltriethoxysilane is 25-26g:500-600mL:120-150mL:10-13g; The carboxylation comprises mixing the silanized graphite powder and the sulfuric acid aqueous solution, stirring and refluxing, controlling the temperature during stirring and refluxing to be 95-100° C., the stirring speed to be 200-400 rpm, and the time to be 22-25 hours, filtering, taking the filter residue, washing it with deionized water for 4-5 times, and vacuum drying it, controlling the vacuum drying temperature to be 80-90° C., and obtaining a reaction accelerator; In the carboxylation, the mass volume ratio of the silanized graphite powder and the sulfuric acid aqueous solution is 25.5-27 g: 5600-6000 mL; The mass concentration of the aqueous sulfuric acid solution is 48%; The equipment is prepared by loading a mixture of a reaction accelerator and quartz sand into a second tubular reactor, then connecting the first tubular reactor and the second tubular reactor in series, with the outlet of the first tubular reactor connected to the inlet of the second tubular reactor; In the equipment preparation, the particle size of the quartz sand is 40 mesh; The volume ratio of the reaction accelerator to the quartz sand is 1:5-5.5; The inner diameters of the first tubular reactor and the second tubular reactor are both 20 mm and the lengths are both 800 mm; The raw material preparation comprises mixing aniline and hydrochloric acid aqueous solution to obtain a first reactant, and mixing sodium nitrite and deionized water to obtain a second reactant; and storing the first reactant and the second reactant at 0-5° C. respectively; In the raw material preparation, the mass ratio of aniline to aqueous hydrochloric acid solution is 400-440:3341-3790; The mass concentration of the hydrochloric acid aqueous solution is 15%; The mass ratio of sodium nitrite to deionized water is 325-360:610.3-697.5; The reaction is carried out by controlling the temperature in the first tubular reactor and the second tubular reactor to 0-5°C, then continuously introducing the first reactant and the second reactant into the inlet of the first tubular reactor at the same time, and after the operation is stable, collecting the product in the second tubular reactor and storing it at 0-5°C; In the reaction, the mass ratio of the first reactant to the second reactant is 8:2, and the total residence time in the first tubular reactor and the second tubular reactor is 47-50s; The test method for stable operation is: if only a trace amount of sulfite is found in the product by potassium iodide starch test paper, it indicates stable operation.
[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The continuous production method of the diazonium salt of the present invention is to react in a first tubular reactor and a second tubular reactor, continuously feed the reactants, and continuously discharge the products, thereby realizing continuous production, and adding a reaction accelerator in the second tubular reactor. The preparation method of the reaction accelerator comprises acid treatment, coating, silylation, and carboxylation. The acid treatment is to wash the graphite powder and then treat it with nitric acid. On the one hand, it can remove impurities in the graphite powder and increase the specific surface area of the graphite powder. On the other hand, it can introduce hydroxyl groups and carboxyl groups on the surface of the graphite powder to obtain acid-treated graphite powder; the coating is to coat the acid-treated graphite powder with silica sol and then perform alkali treatment to obtain a topological structure of silica microspheres coated with silica microspheres. Graphite powder, the graphite powder plays the role of a support, the silica microspheres with a topological structure have high active points and high specific surface area, which are more conducive to modification to obtain coated graphite powder; silanization is to use 2-cyanoethyltriethoxysilane to modify the coated graphite powder, and 2-cyanoethyltriethoxysilane reacts with part of the hydroxyl groups on the surface of the coated graphite powder to introduce cyano groups on the surface of the coated graphite powder to obtain silanized graphite powder; carboxylation is to use sulfuric acid aqueous solution to treat the silanized graphite powder, convert cyano groups into carboxyl groups, neutralize hydroxides on the surface of the silanized graphite powder, and introduce a large number of hydrogen ions on the surface of the silanized graphite powder to obtain a reaction accelerator with strong acidity. During the reaction, the first reactant and the second reactant are mixed to obtain the total reactant, which first enters the first tubular reactor. Since the reaction between hydrochloric acid and sodium nitrite is an inorganic reaction, it will occur quickly. Then, in a weakly acidic environment, the aniline is prevented from reacting with the inorganic acid to form an ammonium salt. Part of the aniline will react with nitrous acid to form a diazonium salt. The mixture flowing out of the first tubular reactor is a mixture of aniline and diazonium salt, and then enters the second tubular reactor. The reaction promoter in the second tubular reactor can ionize hydrogen ions to improve Acidity, thereby promoting the reaction of the remaining aniline with nitrous acid. Since the surface of the reaction promoter is hydrophilic silica, it can also avoid adsorption of aniline, thereby promoting the further reaction of the remaining aniline. After increasing the acidity, the stability of the diazonium salt can be improved, and the irreversible coupling reaction between the diazonium salt and aniline can be avoided. In addition, since the hydrogen ions in the reaction promoter come from the carboxyl group and the hydrogen ions on the surface of silica, the binding ability with aniline is poor, thereby avoiding the formation of ammonium salt from aniline, thereby improving the molar yield of the product and improving the product state; (2) The continuous production method of the diazonium salt of the present invention can reduce the amount of acid used and improve the purity and yield of the prepared diazonium salt. When the molar ratio of aniline to inorganic acid is 1:3.2-3.3, the mass content of diazonium chloride in the obtained product can reach 12.20-12.51%, and the molar yield can reach 96.62-97.13%. DETAILED DESCRIPTION
[0010] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0011] Example 1 A continuous production method of a diazonium salt, specifically: 1. Preparation of reaction accelerator: (1) Acid treatment: 50 g of graphite powder and 470 mL of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 25 kHz for 20 min. The mixture was filtered, the filter residue was vacuum dried at a temperature of 80°C, and then mixed with 500 mL of a 30% nitric acid aqueous solution, and stirred and refluxed at a temperature of 80°C at a stirring speed of 200 rpm for 3 h. The mixture was filtered, the filter residue was washed four times with deionized water, and vacuum dried at a temperature of 80°C to obtain graphite powder after acid treatment. The particle size of the graphite powder is 60 mesh; (2) Coating: 10 mL of ethyl orthosilicate and 500 mL of deionized water were mixed and stirred at a temperature of 20°C and a stirring speed of 200 rpm for 1.5 h. 400 mL of anhydrous ethanol was added and the stirring was continued for 2.5 h. 35 mL of 28% ammonia water was added and the stirring was continued for 2.5 h. 24 g of graphite powder treated with acid was added and the stirring was continued for 30 min. 470 mL of 28% ammonia water was added dropwise at a dropping speed of 10 mL / min. After the addition was completed, the stirring was continued for 11 h. The mixture was filtered and the residue was taken. The residue was washed with deionized water for 4 times and vacuum dried at a temperature of 80°C to obtain the coated graphite powder. (3) Silanization: 25 g of coated graphite powder, 500 mL of anhydrous ethanol and 120 mL of deionized water were mixed, and the mixture was stirred and refluxed. The temperature during stirring and reflux was controlled to be 55°C, the stirring speed was controlled to be 200 rpm, and the time was controlled to be 30 min. 10 g of 2-cyanoethyltriethoxysilane was added, and the mixture was stirred and refluxed for 10 h in a nitrogen atmosphere. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times. The residue was vacuum dried and the vacuum drying temperature was controlled to be 80°C to obtain silanized graphite powder. (4) Carboxylation: 25.5 g of silanized graphite powder and 5600 mL of 48% sulfuric acid aqueous solution were mixed, and the mixture was stirred and refluxed at a temperature of 95°C and a stirring speed of 200 rpm for 22 h. The mixture was filtered, and the residue was washed with deionized water for 4 times, and vacuum dried at a temperature of 80°C to obtain a reaction accelerator. 2. Equipment preparation: Fill the mixture of reaction accelerator and quartz sand into the second tubular reactor, control the volume ratio of reaction accelerator to quartz sand to be 1:5, then connect the first tubular reactor and the second tubular reactor in series, and connect the outlet of the first tubular reactor to the inlet of the second tubular reactor; The particle size of the quartz sand is 40 mesh; The inner diameters of the first tubular reactor and the second tubular reactor are both 20 mm and the lengths are both 800 mm; 3. Raw material preparation: 400 g of aniline and 3341 g of 15% hydrochloric acid aqueous solution were mixed evenly to obtain a first reactant, and 325 g of sodium nitrite and 610.3 g of deionized water were mixed evenly to obtain a second reactant; the first reactant and the second reactant were stored at 0°C respectively; 4. Reaction: Control the temperature in the first tubular reactor and the second tubular reactor to 0°C, then continuously introduce the first reactant and the second reactant into the inlet of the first tubular reactor at the same time, control the mass ratio of the first reactant to the second reactant to be 8:2, and the total residence time in the first tubular reactor and the second tubular reactor to be 50s. After the operation is stable, collect the product in the second tubular reactor and store it at 0°C; The test method for stable operation is: if only a trace amount of sulfite is found in the product by potassium iodide starch test paper, it indicates stable operation.
[0012] In this embodiment, a sample was taken from the product collected after the operation was stabilized and tested. The mass content of diazonium chloride in the product was 12.51%, the molar yield was 96.90%, and the product was a yellow clear liquid without redness.
[0013] The calculation formula of the molar yield in this embodiment is: the mass content of diazonium chloride in the product / (the mass content of aniline in the total reactant after the first reactant and the second reactant are mixed in a mass ratio of 8:2 / 93.13×140.57)×100%.
[0014] Example 2 A continuous production method of a diazonium salt, specifically: 1. Preparation of reaction accelerator: (1) Acid treatment: 52 g of graphite powder and 480 mL of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 25 kHz for 25 min. The mixture was filtered, the filter residue was vacuum dried at a temperature of 85 °C, and then mixed with 520 mL of a 30% nitric acid aqueous solution, and stirred and refluxed at a temperature of 82 °C at a stirring speed of 300 rpm for 3 h. The mixture was filtered, the filter residue was washed four times with deionized water, and vacuum dried at a temperature of 85 °C to obtain graphite powder after acid treatment. The particle size of the graphite powder is 60 mesh; (2) Coating: 10 mL of tetraethyl orthosilicate and 515 mL of deionized water were mixed and stirred at a temperature of 30 °C and a stirring speed of 300 rpm for 1.5 h. 420 mL of anhydrous ethanol was added and the stirring was continued for 2.5 h. 36 mL of 28% ammonia water was added and the stirring was continued for 3 h. 25 g of graphite powder treated with acid was added and the stirring was continued for 35 min. 480 mL of 28% ammonia water was added dropwise at a dropping speed of 12 mL / min. After the addition was completed, the stirring was continued for 11.5 h. The mixture was filtered and the residue was taken. The residue was washed with deionized water for 4 times and vacuum dried at a temperature of 85 °C to obtain the coated graphite powder. (3) Silanization: 25.5 g of coated graphite powder, 550 mL of anhydrous ethanol and 140 mL of deionized water were mixed, and the mixture was stirred and refluxed. The temperature during stirring and reflux was controlled to be 60°C, the stirring speed was controlled to be 300 rpm, and the time was controlled to be 35 min. 12 g of 2-cyanoethyltriethoxysilane was added, and the mixture was stirred and refluxed for 11 h in a nitrogen atmosphere. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times. The residue was vacuum dried and the vacuum drying temperature was controlled to be 85°C to obtain silanized graphite powder. (4) Carboxylation: 26.5 g of silanized graphite powder and 5800 mL of a 48% sulfuric acid aqueous solution were mixed, and the mixture was stirred and refluxed at a temperature of 98°C and a stirring speed of 300 rpm for 23.5 h. The mixture was filtered, and the residue was washed four times with deionized water and vacuum dried at a temperature of 85°C to obtain a reaction accelerator. 2. Equipment preparation: Fill the mixture of reaction accelerator and quartz sand into the second tubular reactor, control the volume ratio of reaction accelerator to quartz sand to be 1:5.2, then connect the first tubular reactor and the second tubular reactor in series, and connect the outlet of the first tubular reactor to the inlet of the second tubular reactor; The particle size of the quartz sand is 40 mesh; The inner diameters of the first tubular reactor and the second tubular reactor are both 20 mm and the lengths are both 800 mm; 3. Raw material preparation: 420 g of aniline and 3563 g of 15% hydrochloric acid aqueous solution were mixed evenly to obtain a first reactant, and 342 g of sodium nitrite and 653.8 g of deionized water were mixed evenly to obtain a second reactant; the first reactant and the second reactant were stored at 2°C respectively; 4. Reaction: The temperature in the first tubular reactor and the second tubular reactor was controlled to 2°C, and then the first reactant and the second reactant were continuously introduced into the inlet of the first tubular reactor at the same time, and the mass ratio of the first reactant to the second reactant was controlled to be 8:2. The total residence time in the first tubular reactor and the second tubular reactor was 49s. After the operation was stable, the product in the second tubular reactor was collected and stored at 2°C; The test method for stable operation is: if only a trace amount of sulfite is found in the product by potassium iodide starch test paper, it indicates stable operation.
[0015] In this embodiment, a sample was taken from the product collected after the operation was stabilized and tested. The mass content of diazonium chloride in the product was 12.30%, the molar yield was 96.62%, and the product was a yellow clear liquid without redness.
[0016] The calculation formula of the molar yield in this embodiment is the same as the calculation method of the molar yield in Example 1.
[0017] Example 3 A continuous production method of a diazonium salt, specifically: 1. Preparation of reaction accelerator: (1) Acid treatment: 55 g of graphite powder and 500 mL of deionized water were mixed, and ultrasonic oscillation was performed at a frequency of 30 kHz for 30 min. The mixture was filtered, the filter residue was vacuum dried at a temperature of 90 °C, and then mixed with 550 mL of a 30% nitric acid aqueous solution, and stirred and refluxed at a temperature of 85 °C and a stirring speed of 400 rpm for 3.5 h. The mixture was filtered, the filter residue was taken, and washed with deionized water for 5 times. The filter residue was vacuum dried at a temperature of 90 °C to obtain graphite powder after acid treatment. The particle size of the graphite powder is 60 mesh; (2) Coating: 11 mL of ethyl orthosilicate and 525 mL of deionized water were mixed and stirred at a temperature of 35 °C and a stirring speed of 400 rpm for 2 h. 450 mL of anhydrous ethanol was added and the stirring was continued for 3 h. 38 mL of 28% ammonia water was added and the stirring was continued for 3 h. 26 g of graphite powder treated with acid was added and the stirring was continued for 40 min. 500 mL of 28% ammonia water was added dropwise at a dropping speed of 15 mL / min. After the addition was completed, the stirring was continued for 12 h. The mixture was filtered and the residue was taken. The residue was washed with deionized water for 5 times and vacuum dried at a temperature of 90 °C to obtain the coated graphite powder. (3) Silanization: 26 g of coated graphite powder, 600 mL of anhydrous ethanol and 150 mL of deionized water were mixed, and the mixture was stirred and refluxed. The temperature during stirring and reflux was controlled to be 65°C, the stirring speed was controlled to be 400 rpm, and the time was controlled to be 40 min. 13 g of 2-cyanoethyltriethoxysilane was added, and the mixture was stirred and refluxed for 12 h in a nitrogen atmosphere. The mixture was filtered, and the residue was washed with anhydrous ethanol for 5 times. The residue was vacuum dried and the vacuum drying temperature was controlled to be 90°C to obtain silanized graphite powder. (4) Carboxylation: 27 g of silanized graphite powder and 6000 mL of a 48% sulfuric acid aqueous solution were mixed, and the mixture was stirred and refluxed at a temperature of 100 °C and a stirring speed of 400 rpm for 25 h. The mixture was filtered, and the residue was washed with deionized water for 5 times, and vacuum dried at a temperature of 90 °C to obtain a reaction accelerator. 2. Equipment preparation: Fill the mixture of reaction accelerator and quartz sand into the second tubular reactor, control the volume ratio of reaction accelerator to quartz sand to be 1:5.5, then connect the first tubular reactor and the second tubular reactor in series, and connect the outlet of the first tubular reactor to the inlet of the second tubular reactor; The particle size of the quartz sand is 40 mesh; The inner diameters of the first tubular reactor and the second tubular reactor are both 20 mm and the lengths are both 800 mm; 3. Raw material preparation: 440 g of aniline and 3790 g of 15% hydrochloric acid aqueous solution were mixed evenly to obtain a first reactant, and 360 g of sodium nitrite and 697.5 g of deionized water were mixed evenly to obtain a second reactant; the first reactant and the second reactant were stored at 5°C respectively; 4. Reaction: The temperature in the first tubular reactor and the second tubular reactor was controlled to 5°C, and then the first reactant and the second reactant were continuously introduced into the inlet of the first tubular reactor at the same time, and the mass ratio of the first reactant to the second reactant was controlled to be 8:2. The total residence time in the first tubular reactor and the second tubular reactor was 47s. After the operation was stable, the product in the second tubular reactor was collected and stored at 5°C; The test method for stable operation is: if only a trace amount of sulfite is found in the product by potassium iodide starch test paper, it indicates stable operation.
[0018] In this embodiment, a sample was taken from the product collected after the operation was stabilized and tested. The mass content of diazonium chloride in the product was 12.20%, the molar yield was 97.13%, and the product was a yellow clear liquid without redness.
[0019] The calculation formula of the molar yield in this embodiment is the same as the calculation method of the molar yield in Example 1.
[0020] Comparative Example 1 On the basis of Example 1, the step of preparing the reaction accelerator in step 1 is omitted, and in the step of equipment preparation in step 2, the step of loading the mixture of the reaction accelerator and quartz sand into the second tubular reactor is omitted, that is, the step of equipment preparation in step 2 is changed to: connecting the first tubular reactor and the second tubular reactor in series, and connecting the outlet of the first tubular reactor to the inlet of the second tubular reactor; The rest of the operations are the same as those in Example 1.
[0021] In the fourth reaction step, samples were taken from the collected product after the operation stabilized and tested. The mass content of diazonium chloride in the product was 11.83%, the molar yield was 91.63%, and the product was red with precipitation.
[0022] The calculation formula of the molar yield in this comparative example is the same as the calculation method of the molar yield in Example 1.
[0023] Comparative Example 2 On the basis of Comparative Example 1, the 3341 g of 15% hydrochloric acid aqueous solution in the raw material preparation step in step 3 was replaced with 3341 g of 22.5% hydrochloric acid aqueous solution, and the remaining operations remained consistent with Comparative Example 1.
[0024] In the fourth reaction step, samples were collected from the product after the operation stabilized and tested. The mass content of diazonium chloride in the product was 12.04%, the molar yield was 93.26%, and the product was a yellow clear liquid without redness.
[0025] The calculation formula of the molar yield in this comparative example is the same as the calculation method of the molar yield in Example 1.
[0026] It can be seen from the molar yield and product state of the product in Examples 1-3 and Comparative Examples 1-2 that the molar yield of the product can be increased and the product state can be improved by loading a mixture of a reaction promoter and quartz sand in the second tubular reactor.
[0027] Unless otherwise specified, all percentages used in the present invention are by mass.
[0028] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A continuous production method of a diazonium salt, characterized in that, The method comprises the following steps: preparing a reaction accelerator, preparing equipment, preparing raw materials, and reacting; The preparation of the reaction accelerator comprises the following steps: acid treatment, coating, silanization, and carboxylation; The acid treatment comprises mixing graphite powder and deionized water, performing ultrasonic vibration, filtering, taking filter residue, vacuum drying, and then mixing with nitric acid aqueous solution, stirring and refluxing, controlling the stirring and refluxing temperature to be 80-85° C., and the time to be 3-3.5 hours, filtering, taking filter residue, washing, and vacuum drying to obtain graphite powder after acid treatment; The coating comprises mixing ethyl orthosilicate and deionized water, stirring the mixture, controlling the stirring temperature to be 20-35° C. for 1.5-2 hours, adding anhydrous ethanol, continuing stirring for 2.5-3 hours, adding the first portion of ammonia water, continuing stirring for 2.5-3 hours, adding the graphite powder after acid treatment, continuing stirring for 30-40 minutes, dropping the second portion of ammonia water, continuing stirring for 11-12 hours after the dropping, filtering, taking the filter residue, washing it, and vacuum drying it to obtain the coated graphite powder; The silanization comprises mixing the coated graphite powder, anhydrous ethanol and deionized water, stirring and refluxing, controlling the temperature during stirring and refluxing to be 55-65° C. for 30-40 min, adding 2-cyanoethyltriethoxysilane, continuing to stir and reflux for 10-12 h in a nitrogen atmosphere, filtering, taking the filter residue, washing it and vacuum drying it to obtain the silanized graphite powder; The carboxylation comprises mixing the silanized graphite powder and the sulfuric acid aqueous solution, stirring and refluxing, controlling the temperature during stirring and refluxing to be 95-100° C. for 22-25 hours, filtering, taking the filter residue, washing it, and vacuum drying it to obtain a reaction accelerator; The equipment is prepared by loading a mixture of a reaction accelerator and quartz sand into a second tubular reactor, then connecting the first tubular reactor and the second tubular reactor in series, with the outlet of the first tubular reactor connected to the inlet of the second tubular reactor; The raw material preparation comprises mixing aniline and hydrochloric acid aqueous solution to obtain a first reactant, and mixing sodium nitrite and deionized water to obtain a second reactant; and storing the first reactant and the second reactant at 0-5° C. respectively; In the reaction, the temperature in the first tubular reactor and the second tubular reactor is controlled to 0-5°C, and then the first reactant and the second reactant are continuously introduced into the inlet of the first tubular reactor at the same time. After the operation is stable, the product in the second tubular reactor is collected and stored at 0-5°C.
2. The continuous production method of diazonium salt according to claim 1, characterized in that In the acid treatment, the mass volume ratio of graphite powder, deionized water, and nitric acid aqueous solution is 50-55 g:470-500 mL:500-550 mL; The particle size of the graphite powder is 60 mesh; The mass concentration of the nitric acid aqueous solution is 30%.
3. The continuous production method of diazonium salt according to claim 1, characterized in that, In the coating, the volume mass ratio of ethyl orthosilicate, deionized water, anhydrous ethanol, the first portion of ammonia water, the graphite powder after acid treatment, and the second portion of ammonia water is 10-11 mL: 500-525 mL: 400-450 mL: 35-38 mL: 24-26 g: 470-500 mL; The mass concentration of the first ammonia water and the second ammonia water are both 28%; The dropping speed of the second portion of aqueous ammonia is 10-15 mL / min.
4. The continuous production method of diazonium salt according to claim 1, characterized in that In the silanization, the mass volume ratio of the coated graphite powder, anhydrous ethanol, deionized water, and 2-cyanoethyltriethoxysilane is 25-26g:500-600mL:120-150mL:10-13g.
5. The continuous production method of diazonium salt according to claim 1, characterized in that, In the carboxylation, the mass volume ratio of the silanized graphite powder and the sulfuric acid aqueous solution is 25.5-27 g: 5600-6000 mL; The mass concentration of the aqueous sulfuric acid solution is 48%.
6. The continuous production method of diazonium salt according to claim 1, characterized in that In the equipment preparation, the particle size of the quartz sand is 40 mesh; The volume ratio of the reaction accelerator to the quartz sand is 1:5-5.5; The inner diameters of the first tubular reactor and the second tubular reactor are both 20 mm, and the lengths are both 800 mm.
7. The continuous production method of diazonium salt according to claim 1, characterized in that, In the raw material preparation, the mass ratio of aniline to aqueous hydrochloric acid solution is 400-440:3341-3790; The mass concentration of the hydrochloric acid aqueous solution is 15%; The mass ratio of sodium nitrite to deionized water is 325-360:610.3-697.
5.
8. The continuous production method of diazonium salt according to claim 1, characterized in that, In the reaction, the mass ratio of the first reactant to the second reactant is 8:2, and the total residence time in the first tubular reactor and the second tubular reactor is 47-50s; The test method for stable operation is: if only a trace amount of sulfite is found in the product by potassium iodide starch test paper, it indicates stable operation.
Citation Information
Patent Citations
Preparation method for low-roughness lithium ion battery graphene-silicon dioxide negative pole plate
CN108199006A
Aromatic amine diazotization reaction conversion rate determination and / or control method in continuous production
CN111077145A
Preparation method of 4,6-diphenylazoresorcinol and 4,6-diaminoresorcinol
CN111848438A
Continuous synthesis method of m-difluorobenzene based on micro-channel reactor
CN112624896A
Automatic-control continuous production device for diazo compound
CN203187607U
